Psychosocial Factors Associated with Treatment Outcomes in Women with Obesity and Major Depressive Disorder who Received Behavioral Activation for Depression - Kern, Daniel (J Behav Med, 2018)
Behavioral activation is an empirically supported treatment for depression, but much is unknown about factors associated with treatment response. The present study aimed to determine whether baseline levels and subsequent changes in psychosocial factors were associated with improvement in depression in women with comorbid obesity who received behavioral activation treatment for depression and a lifestyle intervention. Multilevel modeling was used to estimate the associations between psychosocial factors and change in depression scores during the first 10 weeks of treatment and associations between changes in psychosocial factors from baseline to 6-month follow-up and change in depression over the same time period. No baseline psychosocial factors were associated with depression improvement during treatment (p= 0.110–0.613). However, greater improvement in hedonic capacity (p=0.001), environmental reward (p=0.004), and social impairment (p=0.012) were associated with greater reductions in depression over 6 months. Findings highlight the differential relationship specific psychosocial factors have with depression treatment outcomes.